Transient Leukemoid Reaction from T-Cell Large Granular Lymphocytes Post Autologous Stem Cell Transplant in a Patient Affected by Hodgkin Lymphoma - Andrea Duminuco; Marina Parisi; Giulio Antonio Milone; Alessandra Cupri; Salvatore Leotta; Giuseppe A. Palumbo; Nunziatina Laura Parrinello; Grazia Scuderi; Anna Triolo; Giuseppe Milone (Hematology Reports, 2023)
Monoclonal T-cell lymphocytosis has been reported in patients with concomitant autoimmune diseases, viral infections, or immunodeficiencies. Referred to as T-cell large granular lymphocytic leukemia (T-LGLL), most cases cannot identify the triggering cause. Only small case series have been reported in the literature, and no treatment consensus exists. T-cell lymphocytosis may also appear after the transplant of hematopoietic stem cells or solid organs. Rare cases have been reported in patients undergoing autologous stem cell transplant (ASCT) for hematological diseases (including multiple myeloma or non-Hodgkin’s lymphoma). Here, we describe the singular case of a patient who underwent ASCT for Hodgkin’s lymphoma and displayed the onset of T-LGLL with an uncommonly high number of lymphocytes in peripheral blood and their subsequent spontaneous remission.